Agricultural seasonality, market access, and food security in Sierra Leone - Isaac Bonuedi; Lukas Kornher; Nicolas Gerber (Food Security, 2021)
Seasonal variations in agriculture is a major contributor to undernutrition in many agrarian economies. While recent studies have highlighted the role of markets in improving nutrition, the relative importance of markets in smoothing food consumption across seasons remains largely unexamined. Using data from Sierra Leone, this paper analyses whether access to local food markets mitigates seasonal fluctuations in household dietary diversity and food security. Our results confirm that agricultural seasonality imposes significant fluctuations on household dietary diversity and food security. Households, especially those in rural areas, are found to experience significant deteriorations in dietary diversity and food security during the lean season. Most importantly, the results also show that households with better market access consume more diverse diets and are more food secure in both lean and non-lean seasons than remoter households. An important policy implication of these results is that market-based interventions aimed at strengthening market access through improved market infrastructure and roads can significantly contribute to year-long food consumption smoothing, improved dietary diversity and overall food and nutrition security.
Keywords: Q10; Q13; Q18; I30; 630; Seasonality; Market access; Dietary diversity; Food security; Sierra Leone